Cybersecurity Awareness Amongst Youth - A Survey in Delhi/NCR - Chawla, Vaishali; Kapoor, Yatin; Chawla, Tanya (Indian Journal of Computer Science, 2023)
Cyberspace has become an integral part of modern society, especially in the last two decades. As the internet has rapidly progressed globally, the community of cyber users in cyberspace has widely expanded. One group of cyber users that is swiftly becoming active in cyberspace is the youth, particularly, school and college students. However, young cyber users are increasingly becoming the soft targets of cybercriminals. Taking cognizance of the rising cybercrime cases against young cyber users, this research study surveyed several schools and colleges in the Delhi-NCR region to assess the cyber awareness among students and academic professionals. It was found that most of the participants were not aware of ethical and safe digital practices. These observations are attributed to the poor application of initiatives to ensure cyber safety among school children, especially in developing countries like India. Based on the findings from the survey, this study provides suggestions and recommendations to various role-players involved in cyberspace to assure safe cyber behaviour.